EUROPEAN VECTOR OF DEVELOPMENT OF NON-INSURANCE INTERMEDIARIES IN UKRAINE - A. Sholoiko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
Narrow and broad understanding of the activity of non-insurance intermediaries are suggested. The conсept of the activity of non-insurance intermediaries is disclosed, taking into account the division into main and ancillary activity and their ability to be as outsourcers. A comparison of the insurance and non-insurance intermediaries on the basis of EU legislation is presented. European vector of development of non-insurance intermediaries in Ukraine is defined. It means necessity of implementation of regulation of their ancillary activity related to the distribution of insurance services. Insurance companies and non-insurance intermediaries cooperation in countries of the European Union and Ukraine is characterized.